Interference of weeds on seedlings of four neotropical tree species - Patricia Andrea Monquero; Izabela Orzari; Paulo Vinicius da Silva; Alessandra dos Santos Penha (Acta Scientiarum. Agronomy, 2015)
Seasonal semideciduous forests in southeastern Brazil have experienced intensive fragmentation, and the interference of weeds may affect the dynamics of restored communities. The purpose of this study was to determine if there were specific densities of the weeds Urochloa decumbens and Ipomoea grandifolia at which the growth of seedlings of four Neotropical tree species – Senegalia polyphylla and Enterolobium contortisiliquum (Fabaceae) and Ceiba speciosa and Luehea divaricata (Malvaceae) – would be negatively affected. A randomized experimental design was conducted in a greenhouse, with five treatments to each tree species (different weed densities per pot per tree species) and four replicates per treatment. After the weeds flowered, the height and stem diameter of seedlings were quantified, including the aboveground dry biomass and the percentages of macro and micronutrients contents in the leaves. The growth of the tree seedlings was affected by the lowest weed density (two weeds per pot) when interacting with U. decumbens or I. grandifolia. In general, significant decreases in the percentage of macro and micronutrients in the leaves were observed, especially at eight weeds/pot. Such results could warrant experimental practices in chemical control in conjunction with alternative methods to control of these two weeds in restored areas.